Patterns of Christian-Muslim Encounters in Africa - Azumah, John (The African Christian and Islam, 2013)
During the summer of 2010 Ghana played host to the first ever conference held within Africa to focus solely on the relationship of the African Christian and Islam. The event was led by John Azumah in partnership with the Center of Early African Theology. The conference, chaired by Archbishop John Olorunfemi Onaiyekan of Abuja welcomed over 50 participants from across 27 African countries and several denominations. This book is a collection of the papers presented by 22 of the delegates forming a historical survey and thematic assessment of the African Christian and Islam. In addition, key information on the introduction, spread and engagement of Islam and Christianity within 9 African countries is presented. The book closes with Biblical reflections that opened each day of the conference, providing useful examples of Christians reading the Bible in reference to Islam.
paid
Keywords: Religion / Comparative Religion